Development and Validation of the Nebraska Department of Correctional Services Prison Classification System - Hamilton, Zachary (2016)
Over the last 45 years, the Nebraska Department of Correctional Services (NDCS) has made two substantial changes to its classification system. The first system was created and implemented in the 1970s. In 2005, Patricia Hardyman was contracted to update and modify the classification and reclassification system. Using statistical analyses of available data, a set of prediction models were created to score inmates on items that predicted future infraction behavior. However, the primary issues of the tools were that inmates’ scores were routinely over-classified and that substantial uses of overrides (approximately 40%) were indicated. After a review of the tools’ development methods, several issues were identified, including: a small development sample, a lack of prediction and outcome item specificity, lack of item weighting, a less than optimal feature select strategy, inefficient validation techniques, and the tool’s inability to assess infraction prediction posttransfer. It was therefore determined that this system required major improvements and a research project was outlined and contracted by the University of Nebraska, Omaha